Pengaruh Model Pembelajaran Project Based Learning Terhadap Perkembangan Konsep Diri Mahasiswa - Ahmad Yani (UNIVERSITAS NEGERI MAKASSSAR, 2020)
ABSTRACTThe purpose of this study was to knows the effect of Project Based Learning model on the improvement of developmental Students self concept PJKR Students at STKIP Situs Banten . The method used is Pre experiment with One Group Pretest –Postest Design and samples in this study were 40 of 1st Semester Regular Class PJKR students of STKIP Situs Banten.The processing data used a statistical approach by T test . According to data analysis result, The effect of Project Based Learning model on the improvement of developmental Student self concept PJKR Students at STKIP Situs Banten has a significance value of 0.000. From these results it can be concluded that there are significant effect of learning model on on the improvement of developmental Student self concept PJKR Students at STKIP Situs Banten. So as we can conclude that there are significant effect of project-based learning model on improving of developmental Student self concept PJKR Students at STKIP Situs Banten. According to the result’s analysis, the authors suggest the lecturers and teachers in the learning process, especially in teaching physical education. Researchers recommend using a project-based learning model proven effect on student learning student self concept. And suggest to next research apply to another psychological aspect such as self esteem and self confidence. ABSTRAKTujuan dari penelitian ini adalah untuk mengetahui pengaruh model pembelajaran Project Based Learning terhadap perkembangan konsep diri mahasiswa PJKR STKIP Situs Banten. Metode penelitian yang digunakan adalah pre eksperimen dan sampel dalam penelitian ini adalah mahasiswa PJKR STKIP Situs Banten sebanyak 40 orang. Pengolahan data menggunakan pendekatan statistika dengan teknik uji T. Berdasarkan hasil analisis data, Pengaruh model pembelajaran Project Based Learning terhadap perkembnagan konsep diri mahasiswa PJKR STKIP Situs Banten adalah nilai signifikansi sebesar 0,000. Dari hasil tersebut dapat disimpulkan bahwa terdapat pengaruh model pembelajaran project based learning terhadap perkembangan konsep diri mahasiswa PJRK STKIP Situs Banten. Berdasarkan hasil penelitian tersebut, penulis menyarankan bagi guru dan dosen agar dalam proses pembelajaran khususnya dalam pembelajaran Pendidikan Jasmani. Peneliti merekomendasikan untuk menggunakan model pembelajaran project based learning yang terbukti berpengaruh terhadap perkembangan konsep diri mahasiswa.dan untuk penelitian selanjutya juga peneliti menyarankan untuk mencobakannya pada aspek pskiologis lain seperti self esteem dan dan kepercayaan diri.